Vector Tile Server In Geographic Information System In Bapenda Pekanbaru City - Desy Herlina Citra; Muhammad Jazman; Anofrizen; M Afdal; Arief Rahman (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The Regional Revenue Agency (Bapenda) is an organization primarily focused on regional taxation matters. Bapenda City of Pekanbaru used WebGIS to view spatial data related to taxes. The WebGIS system used in Bapenda is desktop-based. The users of this system must engage directly with GIS hardware in order to get information about taxes, which is a disadvantage of this system. Furthermore, the WebGIS utilized by Bapenda currently relies on WMS (Web Map Service). However, due to the extensive data processing requirements, WMS is not deemed suitable. WMS may result in broken labels, causing confusion among users, and it also has limitations when it comes to styling capabilities. This study's goal is to recommend the use of GIS, specifically the GeoServer and PostGIS programs, for efficient data storage table administration and map digitalization. A Geographic Information System using a Vector Tile Server is the end result of this system. Gaining access to a spatial data infrastructure that works with Vector Tile Server is considered to be beneficial since it will allow spatial data to be presented and styled without placing a heavy load on the client. Implementing GIS, especially GeoServer and PostGIS applications, may make it easier for Pekanbaru City to audit and collect taxes, which will make these responsibilities easier for Pekanbaru City Bapenda.